Taga-F.A. ka ba an analysis on the role of clothing in the stereotyping of selected students from the College of Fine Arts in the University of the Philippines - Barcel, Catherina A.; Maristela, Candy Mae (Quezon City University of the Philippines Diliman, 2024)
In the field of clothing social psychology, clothing is viewed as a form of non-verbal communication that may result to stereotyping groups of people. University of the Philippines-Diliman does not have prescribed uniforms for students which means that there is no straightforward identifier and explicit indicator of which college a student belongs to. This study aims to explore the existence of stereotypes on creative and design students, specifically, on the UP College of Fine Arts and focusing on clothing as an agent of stereotyping. This research is a descriptive type analyzing both qualitative and quantitative data. Focus group discussions and a Snap Judgment Test will be conducted for the data gathering. To determine the existence of stereotyping, the study will consider the perception of the ingroup (UP-CFA students) and the outgroup (students from other colleges). Focus group discussions (FGD) will be conducted for both the ingroup and outgroup using a questionnaire to determine their style and image perception towards themselves and others. A Snap Judgment Test based on Jimenez’ (2014) study on, “The Role of Clothing in Snap Judgments on Sexual Orientation” will be used as a framework for the snap judgment test that this study will conduct for the outgroup. The resulting data will then be analyzed using the following theories and concepts: Attribution Theory, Social Psychology of Clothing, Clothing Behavior, Self-Perception Theory and Social Identity Theory. However, due to the Covid-19 restrictions, this study does not include actual data gathering and analysis but has provided recommendations on the methodology, and the appropriate approach on the presentation and analysis of data. This paper may serve as a guide for further studies on clothing stereotypes and fashion psychology in the University of the Philippines.
In partial fulfillment for the Degree of Bachelor of Science in Clothing Technology
Thesis
Keywords: Stereotype (Social psychology); Clothing; Fashion; Social identity; Clothing behavior; Self-expression.; Fashion psychology